Anisotropic stars in modified gravity: An extended gravitational decoupling approach*SKM and SR acknowledge that this work is carried out under TRC Project (Grant No. BFP/RGP/CBS-/19/099), the Sultanate of Oman. SKM and RN are thankful for continuous support and encouragement from the administration of University of Nizwa. (1st October 2022) - Maurya, S. K.; Mishra, B.; Ray, Saibal; Nag, Riju
Abstract: In this study, we conduct an investigation on decoupling gravitational sources under the framework of gravity. Basically, the complete geometric deformation technique is employed, which facilitates finding the exact solutions to the anisotropic astrophysical system smoothly without imposing any particular ansatz for the deformation function. In addition, we used 5-dimensional Euclidean spacetime in order to describe the embedding Class I spacetime in order to obtain a solvable spherical physical system. The resulting solutions are both physically interesting and viable with new possibilities for investigation. Notably, the present investigation demonstrates that the mixture of + CGD translates to a scenario beyond the pure GR realm and helps to enhance the features of the interior astrophysical aspects of compact stellar objects. To determine the physical acceptability and stability of the stellar system based on the obtained solutions, we conducted a series of physical tests that satisfied all stability criteria, including the nonsingular nature of density and pressure.